The Influence of Eco-Investment on E-Waste Recycling-Evidence From EU Countries - Constantinescu, Andreea; Platon, Victor; Surugiu, Marius; Frone, Simona; Antonescu, Daniela; Mazilescu, Raluca (Frontiers in Environmental Science, 2022)
Waste electrical and electronic equipment is the fastest growing waste stream internationally. Due to its physical characteristics, e-waste is a suitable subject for the development of recovery, repair, and recycling policies, prolonging products’ life cycle for as long as possible, and is an objective pursued by the specific mechanisms of the circular economy. From the point of view of economic development models, e-waste management is one of the areas with significant potential for the implementation of the circular economy. The circular economy is analyzed through a set of 10 indicators that can be found in the Eurostat database. In this paper, we focus on the relationship between two main indicators with significance for this topic (e-waste recycling and eco-investment) and their evolution in European countries. An econometric model regarding the influence of eco-investment on e-waste recycling in EU member states will highlight the impact of circular economy indicators and the importance of promoting the reduce-reuse-recycle paradigm, especially for e-waste. A panel analysis was performed on data from European Union (EU) countries for the period (2008–2018). The analysis uses e-waste recycled per inhabitant as the determined variable and eco-investment per inhabitant as independent variable. The results of the econometric analysis performed show that, although all EU member states benefit from eco-investment, there is a group of countries that have already achieved a high capacity of e-waste recycling, while others should increase eco-investment further.